Relationship Of Financial Leverage On Investment Decisions And Firms' Value: Evidence From Indonesia Manufacturing Companies - Misrah, Misrah; Arifin, Arifin (JAS (Jurnal Akuntansi Syariah), 2024)
This study aims to analyze and empirically test the impact of financial leverage on investment decisions, firms' value, and the role of investment decisions as a mediator. This study uses a quantitative approach with secondary data. Manufacturing companies listed on the Indonesia Stock Exchange in 2016-2022 are the research population. Sampling was done using purposive sampling, and a sample of 117 companies was obtained. The data analysis technique used structural equation modeling. The study's results showed that leverage did not affect investment decisions. However, leverage showed a positive effect on firms' value. Investment decisions have a positive effect on firms' value. Investment decisions can mediate the effect of leverage on firms' value. This study theoretically offers a framework for understanding the role of financial leverage on firm value through investment decisions. In addition, this study can be a reference for further research. Practically, this study can be a reference for investors in choosing stock investments and stakeholders in manufacturing companies to overcome obstacles, maximize market value, and optimize capital structure.